Enhanced Viscosity of Aqueous Palygorskite Suspensions through Physical and Chemical Processing - Feng-shan Zhou; Tian-qi Li; Yun-hua Yan; Can Cao; Lin Zhou; Yang Liu (Advances in Materials Science and Engineering)
Palygorskite has remarkable rheological properties and was used to increase the stability and viscosity of aqueous suspensions. The effects of different physical and chemical processing methods on the apparent viscosity and plastic viscosity of the palygorskite suspensions such as pressing, ultrasound scattering, acidification, and chemical additives have been released. The pressing and ultrasound scattering indicated that the dispersed state of palygorskite could be increased effectively after treatment, and the apparent viscosity of treated-palygorskite samples increased almost 2-3 times compared to that of before. The viscosity of the acid-treated palygorskite suspension was not increased. The viscosity increased with the content of bentonite in the mixture of bentonite and palygorskite in fresh water. It seemed to be not worthy to add a certain amount of bentonite to palygorskite in order to enhance viscosity and vice versa. Chemical additives appeared to have good effects on the rheological behavior of palygorskite suspension. Magnesium oxide revealed great contribution to viscosity enhancement. The main mechanism was the electrostatic attractive interaction between magnesium oxide particles with positive charges and the palygorskite rods with negative charges. This interacted force has an impact on the structural inversion of palygorskite rods and even caused the reinforcing of flocculation.